Elmo N. Pickerill papers - Pickerill, Elmo N. (Elmo Neale), 1885-1968.
Correspondence, printed matter, photographs, and other papers relating to Pickerill's career as an aviator and to early aviation in the U.S., particularly Long Island, N.Y. Subjects include air mail; air meets, races, and exhibitions; and experimentation with autogiros, helicopters, and parachutes. Includes material pertaining to aeronautics clubs including the Early Birds of Aviation, Long Island Early Fliers Club, Ox-5 Club of America, Quiet Birdmen, and the Wings Club (New York, N.Y.). Persons represented include Tom Benoist, Edward R. Boland, Glenn Hammond Curtiss, William A. Denehie, Wallace P. Dunmore, Amelia Earhart, Viola Gentry, Kyung O. Kim, Charles A. Lindbergh, William Mitchell, Wiley Post, Marjorie Claire Stinson, Chance Vought, Waldo Dean Waterman, Orville Wright, and Wilbur Wright.
Aviator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Benoist, Tom; Boland, Edward R., -- 1892-1967.; Curtiss, Glenn Hammond, -- 1878-1930.; Denehie, William A. -- 1891-1974.; Dunmore, Wallace P; Earhart, Amelia, -- 1897-1937.; Gentry, Viola, -- -1988.; Kim, Kyung O; Lindbergh, Charles A. -- 1902-1974.; Mitchell, William, -- 1879-1936.; Post, Wiley, -- 1898-1935.; Stinson, Marjorie Claire, -- 1896-1975.; Vought, Chance, -- 1890-1930.; Waterman, Waldo Dean, -- 1894-1976.; Wright, Orville, -- 1871-1948.; Wright, Wilbur, -- 1867-1912.; Early Birds of Aviation (Organization); Long Island Early Fliers Club; Ox-5 Club of America; Quiet Birdmen; Wings Club (New York, N.Y.); Aeronautics; Aeronautics -- United States; Aeronautics -- New York (State) -- Long Island; Aeronautics -- Exhibitions; Aeronautics -- Societies, etc; Air mail service; Air shows; Airplane racing; Autogiros; Helicopters; Parachutes; Aviators